2022
DOI: 10.1088/1755-1315/1081/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a ship with the self-righting moment in extreme condition

Abstract: Patrol vessel is an essential part of offshore security archipelago countries such as Indonesia. The main feature of patrol vessel is operating in rough waves during operation. Ship stability is one of the challenging aspects of patrol vessel because, in extreme conditions, the ship can capsize due to losing a self-righting moment. The present paper carried out a study of a patrol vessel with a self-righting moment in extreme conditions. The condition is a ship with rolling up to above 180°. Thus, the ship can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The self-righting moment is a concept where the ship can return to its upright position after being upside down to a certain degree or even completely upside down (180°) without the help of an external force. The previous study of a patrol boat with an effective self-righting moment was performed using experimental and numerical methods [1,2]. The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The self-righting moment is a concept where the ship can return to its upright position after being upside down to a certain degree or even completely upside down (180°) without the help of an external force. The previous study of a patrol boat with an effective self-righting moment was performed using experimental and numerical methods [1,2]. The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases.…”
Section: Introductionmentioning
confidence: 93%
“…This influence can be seen from the area of the stability arm curve (GZ curve), where the elevation of the superstructure affects the maximum GZ magnitude and the angle at which the maximum GZ [13]. The present study is based on previous works [1], i.e., a patrol boat with four variations using different deckhouse heights where there are heights of 2.01 m to a height of 2.31 m with a difference of 0.1 m each. The analysis results showed that the condition of the ship with the lowest deckhouse height does not have an excellent self-righting IOP Publishing doi:10.1088/1755-1315/1298/1/012004 2 moment compared to the other variations, whereas in a fully loaded condition, a patrol boat with a deckhouse of 2.01 m has a negative moment at an angle at 17°.…”
Section: Introductionmentioning
confidence: 99%